1999
DOI: 10.1097/00005392-199907000-00111
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Medicine. First of Two Parts. Blood Transfusion

Abstract: No AbstractEditorial Comment: Attitudes regarding blood transfusion are changing rapidly and the authors cover some of the relevant issues. Better screening of donors has dramatically decreased the risk of transmission of viral infections, such as human immunodeficiency virus and hepatitis C. There also is increasing information that lower hemoglobin levels are acceptable in patients without cardiac disease. Leukocyte reduction blunts transfusion mediated immunosuppression but its routine performance is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
300
2
18

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(324 citation statements)
references
References 0 publications
4
300
2
18
Order By: Relevance
“…16 Beyond these risks, blood transfusions always carry a small risk of viral transmission, bacterial contamination, or hemolytic reactions. 17 The mechanism causing some of these adverse reactions seems diffuse and systemic. Blood transfusions may cause a systemic inflammatory response, induce nonspecific immunosuppression, and may cause tissue hypoxemia by occluding microvasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Beyond these risks, blood transfusions always carry a small risk of viral transmission, bacterial contamination, or hemolytic reactions. 17 The mechanism causing some of these adverse reactions seems diffuse and systemic. Blood transfusions may cause a systemic inflammatory response, induce nonspecific immunosuppression, and may cause tissue hypoxemia by occluding microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Some have also suggested that blood-donor antibodies can cause the recipient's neutrophils to react, leading to increased pulmonary microcirculation permeability and to acute lung injury. 17 Thus, the mechanisms underlying adverse Values presented as percentages. a Median nadir hemoglobin = 10.0 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…However, many real and perceived risks are associated with the procedure, such as infection, allergic and/or febrile reactions, and the theoretical risk of transfusion-associated immunosuppression (Ludwig and Fritz, 1998a;Goodnough et al, 1999) (Table 1). In addition, there is the inconvenience, to both clinician and patient, of administering the transfusions for only transient benefit.…”
Section: Inadequacies In the Current Treatment Optionsmentioning
confidence: 99%
“…Although infrequent, allogeneic transfusions carry important medical risks, including bloodborne infections, allergic and hemolytic reactions, and transfusion-associated sepsis [2,15,16,18,36,37,41]. Transfusion of preoperatively donated autologous blood is a theoretically safer, yet more costly and logistically difficult alternative [2,18,32].…”
Section: Introductionmentioning
confidence: 99%